Eating Behaviour and Social Media Addiction among Secondary School Students in Kuantan, Pahang - Adnan, Khalisah; Rusali, Roszanadia; Hamirudin, Aliza Haslinda; Wan Mahmood, Wan Fathin Fariza (International Journal of Allied Health Sciences, 2025)
Background: Social media has become integral to adolescents’ lives, shaping their eating behaviours through exposure to unregulated content. Visually appealing but energy-dense, lack of nutrient foods is frequently promoted, influencing adolescents at a formative stage of behaviour development. In Malaysia, the double burden of malnutrition persists alongside unhealthy eating habits. This study aimed to assess eating behaviours and social media addiction among secondary school students in Kuantan, Pahang. Methods: A cross-sectional study was conducted among 140 students aged 13 to 15 years at SMK Air Putih, Kuantan, Pahang, using convenience sampling. Data were collected through sociodemographic questions, anthropometric measurements, the Dutch Eating Behaviour Questionnaire (DEBQ) and the Social Media Addiction Scale-Student Form (SMAS-SF). Results: Mean scores for eating behaviours were 20.86 ± 8.17 (restrained eating), 22.18 ± 8.56 (emotional eating) and 25.35 ± 7.35 (external eating), with external eating being the most prevalent. Social media addiction levels were classified as non-addicted (15.0 %), low addicted (37.1 %), moderately addicted (45.0 %) and highly addicted (2.9 %). Conclusion: External eating was the most common behaviour, followed by emotional and restrained eating. Most students were moderately addicted to social media, while only a small proportion were non-addicted. These findings underscore the need for greater awareness of healthy lifestyles and targeted interventions to mitigate social media addiction while promoting healthy eating habits.